Epochal Role of Women’s Education to Reduce the Severity of Domestic Violence in Nepal: Evidence from Nepal Demographic and Health Survey 2016 - Rai, Mahendra Kumar (Humanities and Social Sciences Journal, 2021)
Violence against women is a deleterious violation of human rights. Despite having the different policy and legal provisions, the incident of domestic violence is still exacerbating in Nepal. The main purpose of this paper is to examine the significant role of education for reducing physical, sexual and emotional violence against women. The study uses the data of Nepal Demographic and Health Survey 2016 which focuses on the 4,444 women ages 15 to 49 years having multiple background characteristics. Mainly, univariate, bi-variate and logistic regression analysis is applied to analyze the data. There is an inverse relationship between the level of education and the degree of violence. The level of education has the strongest and positive effect on reducing violence. The higher level of education has significant effect on reducing physical violence [pushed, shook or had something thrown (OR=0.27, CI: 0.16-0.43), slapped (OR=0.17, CI: 0.12-0.26) and kicked or dragged (OR: 0.11, CI: 0.05-0.23)], sexual violence [physically forced into unwanted sex (OR=0.35, CI: 0.19-0.62) and in forced into other unwanted sexual acts (OR=0.22, CI: 0.08-0.61)] and emotional violence [humiliation (OR=0.28, CI: 0.15-0.50), threat (OR=0.16, CI: 0.07-0.41) and insult (OR=0.36, CI: 0.22-0.58). There is an inverse relationship between the level of education and violence against women in Nepal. Women with higher level of education have significantly contributed to reducing either type of violence and vice versa. So, women’s education can be regarded as a prominent contributing factor for reducing domestic violence in Nepal.